The determinants of rising informality in Brazil: evidence from gross worker flows - Mariano Bosch; Edwin Goni; William F. Maloney (Institute for the Study of Labor (IZA), 2007)
This paper studies gross worker flows to explain the rising informality in Brazilian metropolitan labor markets from 1983-2002. This period covers two economic cycles, several stabilization plans, a far-reaching trade liberalization, and changes in labor legislation through the Constitutional reform of 1988. Focusing first on cyclical patterns, we confirm Bosch and Maloney's (2006) findings for Mexico that the patterns of worker transitions between formality and informality correspond primarily to the job-to-job dynamics observed in the US and not to the traditional idea of informality constituting the inferior sector of a segmented market. However, we also confirm distinct cyclical patterns of job finding and separation rates that lead to the informal sector absorbing more labor during downturns. Second, focusing on secular movements in gross flows and the volatility of flows, we find the rise in informality to be driven primarily by a reduction in job finding rates in the formal sector. A small fraction of this is driven by trade liberalization, and the remainder seems driven by the rising labor costs and reduced flexibility arising from Constitutional reform.
Keywords: 330; Städtischer Arbeitsmarkt; Ballungsraum; Informeller Sektor; Brasilien